A novel congenital disorder of glycosylation type without central nervous system involvement caused by mutations in the phosphoglucomutase 1 gene. Issue 3 (14th September 2012) - Pérez, Belén; Medrano, Celia; Ecay, Maria Jesus; Ruiz‐Sala, Pedro; Martínez‐Pardo, Mercedes; Ugarte, Magdalena; Pérez‐Cerdá, Celia
Abstract: Recent years have seen great advances in our knowledge of congenital disorders of glycosylation (CDG), a clinically and biochemically heterogeneous group of genetic diseases caused by defects in the synthesis (CDG‐I) or processing (CDG‐II) of glycans that form glycoconjugates. This paper reports a new subtype of non‐neurological CDG involving the impaired cytoplasmic biosynthesis of nucleotide sugars needed for glycan biosynthesis. A patient presented with muscle fatigue, elevated creatine kinase, growth hormone deficiency, and first branchial arch syndrome. These findings, together with the abnormal type II plasma transferrin isoform profile detected, was compatible with a CDG. Functional testing and clinical analyses suggested a deficiency in the interconversion of glucose‐1‐phosphate and glucose‐6‐phosphate catalyzed by phosphoglucomutase (PGM1), a defect previously described as glycogenosis type XIV (GSDXIV, MIM 612934). PGM1 activity in patient‐derived fibroblasts was significantly reduced, as was the quantity of immunoreactive PGM1 protein (Western blot assays). Mutation analysis of PGM1 and subsequent functional analysis investigating transient expression of PGM1 in immortalized patient fibroblasts, followed by ex vivo splicing assays using minigenes, allowed the characterization of two novel pathogenic mutations: c.871G>A (p.Gly291Arg) and c.1144 + 3A>T. The latter represents a severe splicing mutation leading to the out‐of‐frame skipping of exon 7 and the formation of a truncated protein (p.Arg343fs). MALDI mass spectra of permethylated protein N‐glycans from the patient's serum suggested a marked hypoglycosylation defect. The present findings confirm that, in addition to a rare muscular glycolytic defect, PGM1 deficiency causes a non‐neurological disorder of glycosylation.